Quality of Life in Children with Epilepsy in Wah Cantt, Pakistan: A Cross-sectional Study - Shahzad Haider , Tahir Mahmood , Sajjad Hussain , Sajid Nazir , Sidra Shafiq , Alina Hassan (Journal of Rawalpindi Medical College, 2020)
Objective: To assess the Quality Of Life (QOL) in children with epilepsy using modified QOLCE-55 questionnaire. Material and Methods: We consecutively enrolled children aged 4 to 16 years who were under treatment for childhood epilepsy. Basic demographic and clinical details including type of epilepsy, developmental history, family history of epilepsy and any co-morbidity were recorded in a predesigned Performa. QOL was evaluated by using modified QOLCE-55 (39 items) from parents. Results: A total of 54 children were enrolled in the study, 42 (78%) were males and 12(22%) were female children with epilepsy. Eight children got good QOLCE score, while 24 children had average and 22 children got a poor score. The good score was mostly seen in 4-8 years (40%) of age while the poor score was seen in 12-16 years (70%) age group. Age of the patients (p=<0.001), gender (p=<0.001), associated co-morbidities (p=0.003) and family history of epilepsy (p=0.011) showed a significant effect on the QOLCE score. Type of epilepsy (p= 0.825) and development of a child (p=0.109) did not affect the QOLCE score significantly. Conclusion: The study showed that Children with co-morbidities, family history of epilepsy and female children of older age group (12-16 years) had poor QOL. Types of seizures and development of the child did not significantly alter the QOLCE score.